Burden of Acute-Care Hospitalization for Community-Acquired Pneumonia in Canadian Adults Aged 50 Years or Older: Focusing on Most Responsible Diagnosis Tells Only Part of the Story - Ana Gabriela Grajales Beltrán; Derek Lytle; Jelena Vojicic; Prerna Grover; Lidija Latifovic; Shane Golden; Juejing Ling; Brad Millson; Alejandro Cane (Vaccines, 2023)
The burden of all-cause community-acquired pneumonia (CAP), including pneumococcal pneumonia, is typically estimated using ICD codes where pneumonia is coded as the most responsible diagnosis (MRDx). Pneumonia may also be coded as other than most responsible diagnosis (ODx) based on administrative and reimbursement criteria. Analyses including pneumonia as MRDx only likely underestimate hospitalized CAP incidence. The aim of this study was to estimate the burden of hospitalized all-cause CAP in Canada and to assess the contribution of ODx-coded cases to the overall disease burden. This longitudinal retrospective study obtained data from the Canadian Institutes of Health Information (CIHI) for adults 50+ years hospitalized for CAP between 1 April 2009 and 31 March 2019. Cases were identified as those where pneumonia was either diagnosis code type M (MRDx) or pre-admit comorbidity type 1 (ODx). Reported outcomes include pneumonia incidence rate, in-hospital mortality, hospital length of stay, and cost. Outcomes were stratified by age group, case coding, and comorbidity. Between 2009–2010 and 2018–2019, CAP incidence increased from 805.66 to 896.94 per 100,000. During this time, 55–58% of cases had pneumonia coded as ODx. Importantly, these cases had longer hospital stays, higher in-hospital mortality, and higher cost of hospitalization. The burden of CAP remains substantial and is significantly greater than that estimated by solely focusing on MRDx-coded cases. Our findings have implications for policy decision making related to current and future immunization programs.